Teachers’ technological (pedagogical) knowledge–predictors for students’ ICT literacy? - Kastorff, Tamara; Stegmann, Karsten (Frontiers in Education, 2024)
With the integration of information and communication technologies (ICT) into curricula, teachers are responsible for promoting ICT literacy among secondary school students, which requires in-depth technological knowledge (TK) and technologicalpedagogical knowledge (TPK) on the part of teachers. This study uses a multilevel analysis to examine how teachers' professional knowledge at TK and TPK influences secondary school students' ICT literacy. Using data from n = 1,566 students from a larger sample taught in N = 134 classes by N = 220 teachers in N = 39 schools, our results show contrary to our hypotheses, no significant relationship between teachers' professional knowledge regarding TK and TPK and students' cross-curricula ICT literacy. Furthermore, we did not find any significant relationship in our model between students' study-related ICT use and ICT literacy. By analyzing the relationship between teachers' TK and TPK and students' ICT literacy, our study provides new insights into the relationship between teachers' cross-curricular knowledge and students' crosscurricular achievements. It discusses further possible explanations and directions for future research.